Detection of Cecropin B by liquid-crystal biosensor based on AuNPs signal amplification. Issue 12 (25th September 2020) - Su, Xiuxia; Xu, Jia; Zhang, Jing; Yang, Dong; Huo, Wenjing; He, Chen
ABSTRACT: A novel biosensor was prepared by using gold nanoparticles (AuNPs) signal amplification technology combined with liquid crystal biosensor to detect Cecropin B (CB). The surface of the substrate was modified with (3-aminopropyl)-triethoxysilane/ N, N -dimethyl- N -octadecyl-(3-aminopropyl)-trimethoxysilyl chloride (APTES/DMOAP), glutaraldehyde (GA) as crosslinking, the AuNPs and Cecropin B antibody (anti-CB) complex could be fixed on the basal surface. CB and anti-CB can bind to make the liquid crystal (LC) changes in a vertical orientation, so as to achieve the purpose of testing. The volume of AuNPs is much larger than that of CB and anti-CB, thus AuNPs can play the role of signal amplification. Compared to the experiments without nano-gold amplification, our method has a lower detection limit. Finally, the limit of CB detection could be as low as 1.49 × 10 −2 ng/mL. This method has the advantages of good specificity, high sensitivity, low detection limit and simple operation. Graphical abstract: uf0001